2015
DOI: 10.1093/jb/mvv028
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive retinoid isomerase activity of RPE65 mutants associated with Leber Congenital Amaurosis

Abstract: RPE65 is a membrane-associated retinoid isomerase involved in the visual cycle responsible for sustaining vision. Many mutations in the human RPE65 gene are associated with distinct forms of retinal degenerative diseases. The pathogenic mechanisms for most of these mutations remain poorly understood. Here, we show that three Leber congenital amaurosis -associated RPE65 mutants (R91W, Y249C and R515W) undergo rapid proteasomal degradation mediated by the 26 S proteasome non-ATPase regulatory subunit 13 (PSMD13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…6d, right). Detailed read distribution of RIP-seq and polysome-bound RNA-seq analyses showed that the genomic regions of transcripts functioning in the response to oxygen levels, such as ALDH2 [20], ADAM17 [21] and P4HA1 [22], or which are involved in cancer/ catabolic pathways, such as Procollagen-Lysine,2-Oxoglutarate 5-Dioxygenase 1 (PLOD2 [23], FGF9 [12], DCUN1D5 [24], CKS1B [25] and PSMD13 [26], were bound by hnRNPM and that their polysome-bound reads were up-regulated by hypoxia treatment (Fig. 6e and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6d, right). Detailed read distribution of RIP-seq and polysome-bound RNA-seq analyses showed that the genomic regions of transcripts functioning in the response to oxygen levels, such as ALDH2 [20], ADAM17 [21] and P4HA1 [22], or which are involved in cancer/ catabolic pathways, such as Procollagen-Lysine,2-Oxoglutarate 5-Dioxygenase 1 (PLOD2 [23], FGF9 [12], DCUN1D5 [24], CKS1B [25] and PSMD13 [26], were bound by hnRNPM and that their polysome-bound reads were up-regulated by hypoxia treatment (Fig. 6e and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Before and after incubating with antibodies, the cells were washed with 0.1% Tween‐20/PBS three times. Images were captured with a Zeiss LSM710 Meta confocal microscope with a 40× oil‐immersion objective .…”
Section: Methodsmentioning
confidence: 99%
“…Protein misfolding and mis-localization have been reported as the primary cause of pathology in band keratopathy, a recessive condition similar to IRD due to the involvement of ASRGL1 mutation (23). In addition, protein misfolding, intracellular misrouting and accumulation of misfolded proteins in cells have been reported in dominant and recessive retinal degenerations and neurodegenerations (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%